A modified compliance method for fatigue crack propagation applied on a single edge notch specimen. (November 2016) - Ewest, D.; Almroth, P.; Sjödin, B.; Simonsson, K.; Leidermark, D.; Moverare, J.
Highlights: A modified compliance crack length method suitable for e.g. TMF testing. Experimental investigation of crack length measurements via heat tinting. Numerical investigation of crack initiation and propagation effects on stiffness. Good correlations between the numerical and experimental results. New modified compliance calibration curve for a single edge notch specimen. Abstract: Crack length measurements with high accuracy are often difficult to achieve during fatigue crack propagation testing under non-isothermal conditions. In this work a modified approach to the compliance method defined in e.g. ASTME647 is described, which is better suited for high loads, varying temperatures and for taking the scatter in Young's modulus into account. A numerical finite element study is performed for a single edge notch specimen, to investigate the influence of initiation locations on the accuracy of the method. The change in cracked area versus change in stiffness for three different cases are numerically shown to collapse to one curve, i.e. the result is not significantly affected by how the crack is initiated. The numerical study is compared to results from two experiments using different materials, with heat tinting during the tests for extracting snapshots of the crack fronts. A good agreement between the experiments and the numerical study is shown. A new compliance curve and a new geometry function for the stress intensity factor is proposed for the single edge notch specimen.